Non-Dose-Dependent Relationship between Antipredator Behavior and Conspecific Alarm Substance in Zebrafish - Yaxi Li; Zhi Yan; Ainuo Lin; Xiaodong Li; Ke Li (Fishes, 2023)
A series of behavioral detection paradigms have been developed for zebrafish (Danio rerio) to examine anxiety-like behavioral responses. Among them, the novel tank diving test is rapidly gaining popularity in translational neuroscience and behavioral research for the investigation of psychopharmacological activity focusing on stress. Zebrafish respond to conspecific epidermal-released alarm substances with antipredator reactions. Although the alarm responses of zebrafish were well characterized in a novel tank diving experiment, the relationship between the intensity of the alarm behavior and the concentration of the alarm substance needed to be understood more adequately. In the current paper, we investigated the behavioral phenotypes and potencies of zebrafish elicited by the serial dilution of an alarm substance in the novel tank diving test. Using a video-tracking assisted behavioral quantification approach, we demonstrated no linear concentration-dependent relationship between antipredator behavior and skin extracts, suggesting that an optimal concentration induced each typical behavioral response. The results showed that the freezing duration (%) significantly increased when stimulated with 104-fold times dilutions of skin extract (equivalent 5 × 10−5 fish/L), while erratic movements (%), time in the bottom half (%), and latency to the upper half (s) significantly elevated when stimulated with 103-fold times dilutions (equivalent 5 × 10−4 fish/L). Therefore, the concentration threshold for an alarm substance that elicited innate fear behavior in zebrafish was presumed to be an equivalent concentration of approximately 5 × 10−4 fish/L. The conclusions may fill a knowledge gap between the innate fear response triggered by injured skin and a novel tank diving paradigm that provides insights into the characterization of alarm substance, behavioral responses, and physiological response mechanisms in zebrafish.